Assessment of Open Defecation in Primary Schools in Sokoto State, Nigeria - Abdulkarim, Hauwa'u Mukhtar; Abubakar, Jabir; Muhammad, Abubakar (Darul Yasin Al Sys, 2024)
Open defecation is a threat to public health and the education of children at schools. This study assessed open defecation among primary schools in Sokoto Nigeria using a survey study. 300 questionnaires were filled during a random visit of primary schools in the Sokoto. The possible causes/ factors that led to open defecation in primary schools in Sokoto, Nigeria are: absence of water supply (40.0%), dilapidated toilets (40.0%), and untidy toilets; therewith, no school was found without toilet (0.0%). Regards to practice of open defecation in primary schools in Sokoto, Nigeria; in majority of the schools visited (80.0%), there was presence of feces in some parts of the schools’ surroundings, and minority of the schools (20.0%) had no feces on their surroundings when visited. Mostly the feces found was dry (80.0%), and few are fresh (20.0%). Majority (50.0%) of the schools had no any water supply in their premises, 25.0% had protected water supply, and 25.0% had unprotected water supply at the premises. Possible solutions to control open defecation among students of primary schools were suggested: the majority of the respondents (41.7%) suggested provision of enough toilets, and guidance/ health education (33.3%); and minority among them (25.0%) suggested provision of clean water supply. Governments should provide enough water supply, enough toilets and related hardware, and there is need for cleaners and proper health ed8cation of students/ pupils on importance of hygiene and sanitation.